2020
DOI: 10.1111/ajae.12113
|View full text |Cite
|
Sign up to set email alerts
|

Links between Maternal Employment and Child Nutrition in Rural Tanzania

Abstract: Improving child nutrition and empowering women are two important and closely connected development goals. Fostering female employment is often seen as an avenue to serve both these goals, especially if it helps to empower the mothers of undernourished children. However, maternal employment can influence child nutrition through different mechanisms, and the net effect may not necessarily be positive. We develop a theoretical model to show that maternal employment can affect child nutrition through changes in in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 44 publications
(46 reference statements)
4
39
0
Order By: Relevance
“…This finding is also evidenced by the significant number of indicators [36] on women and quality diets. This finding is consistent with the vast literature on maternal and child nutrition and health [38][39][40][41]. The heavy workloads women carry mean that they typically have high nutrient requirements.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…This finding is also evidenced by the significant number of indicators [36] on women and quality diets. This finding is consistent with the vast literature on maternal and child nutrition and health [38][39][40][41]. The heavy workloads women carry mean that they typically have high nutrient requirements.…”
Section: Discussionsupporting
confidence: 88%
“…Attention to women and children's nutrition during the first thousand days of a child's life-from conception until age two-is prioritised [30]. Consequently, much of the literature on diets in Africa is centred around improving maternal and child nutrition [38][39][40][41][42]. An overemphasis on women has undermined men's nutrition, overlooking important gender dynamics related to hegemonic masculinity and the significant implications of these on household food and nutrition security.…”
Section: Food Environmentmentioning
confidence: 99%
“…Improved household socioeconomic conditions can influence child nutrition through: (i) higher household income, (ii) improved household purchasing power for foodstuffs, and (iii) improved knowledge and childcare practices [ 1 , 99 , 100 , 101 ]. This study indicates that children who resided in socioeconomically improved households (i.e., wealthy households or having formally employed mothers/caregivers) were less likely to be stunted.…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing such aspects in more detail is beyond the scope of this study. Another recent study with data from Tanzania showed that female off-farm employment contributes to an increase in female bargaining power and has non-linear effects on child nutrition (Debela, Gehrke, & Qaim, 2020). the use of hired labor.…”
Section: 5mentioning
confidence: 99%